1971
DOI: 10.1063/1.1675625
|View full text |Cite
|
Sign up to set email alerts
|

Radiative and Collisional Transitions between Coupled Vibrational Modes of CO2

Abstract: Each of the two energy levels of CO2 at 1388 and 1285 cm−1 is an equal mixture of doubly excited bending mode and singly excited symmetric stretch mode. The collision numbers of these levels for CO 2–CO 2 collisions are calculated by using the mixed wavefunctions in conjunction with the SSH theory that has been expanded to include two-quantum transitions. This relaxation is shown to take place via various near resonant V-V processes at transition rates of the order of 10 4 sec −1 · torr−1. In particular, direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1973
1973
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In an early experiment, Rhodes et al [1968] indicated a rate of relaxation of the 10 0 0 level in V‐V CO 2 exchange of 1.15 × 10 −11 cm 3 s −1 , although they pointed out that they could not distinguish if the 02 2 0 level was involved. Later interpretations of that experiment [ Seeber , 1971] proposed that the rate measured by Rhodes et al was more likely not related to our process 4. Additionally, Seeber calculated a rate for the 02 2 0 state relaxation leading to a combined relaxation rate of the 020 states of 1.6 × 10 −11 cm 3 s −1 .…”
Section: Kinetic Parameter Uncertainty Ranges and Errors On Saber Tkmentioning
confidence: 65%
“…In an early experiment, Rhodes et al [1968] indicated a rate of relaxation of the 10 0 0 level in V‐V CO 2 exchange of 1.15 × 10 −11 cm 3 s −1 , although they pointed out that they could not distinguish if the 02 2 0 level was involved. Later interpretations of that experiment [ Seeber , 1971] proposed that the rate measured by Rhodes et al was more likely not related to our process 4. Additionally, Seeber calculated a rate for the 02 2 0 state relaxation leading to a combined relaxation rate of the 020 states of 1.6 × 10 −11 cm 3 s −1 .…”
Section: Kinetic Parameter Uncertainty Ranges and Errors On Saber Tkmentioning
confidence: 65%
“…Briefly, SSH assumes that strong, short-range, repulsive forces are effective in producing vibrational transitions. In practice, this theory leads to relatively simple expressions for the state-specific relaxation rates [39,40]. They are sometimes used for quantitative comparison with experimental determinations in the absence of any other better theoretical estimations, or, especially, for the scaling of the rate coefficients with quantum numbers over a very limited number of known coefficients.…”
Section: Estimation Of Vibrational Rates (General Overview)mentioning
confidence: 99%
“…In this work, apart from V-T and V-V, we have investigated the influence of spontaneous emission. Overall, these processes can be grouped into the following categories: Extended versions of the original SSH theory include two-quantum transitions (see [40] for more details).…”
Section: Elementary Processesmentioning
confidence: 99%